Iron hydrous oxide isopropanolic gel. solvothermal treatment - Carvalho, Eduardo L. C. N.; Junior, Miguel Jafelicci [UNESP] (Taylor & Francis, 1991)
Iron hydrous oxide gel was sol vothermal ly treated in Pyrex sealed ampoule under pressure of 500 bar and temperature of 300°C. Additives like acetic acid, sodium acetate and sodium citrate were used as mineralizers. Chemical analysis, X-ray powder diffraction (XRD), vibrational infrared spectroscopy and scanning electron microscopy techniques were used for characterization of products. © 1991, Taylor & Francis Group, LLC. All rights reserved.